Pharmacokinetic study of Q808 in rhesus monkey using liquid chromatography–tandem mass spectrometry - Xiao, Ning; Li, Xiang; Li, Wei; Zhao, Jialin; Li, Yingnan; Wang, Limei (Frontiers in Pharmacology, 2024)
Background: Q808 is a novel antiepileptic agent currently in development. In this study, we established and validated a LC-MS/MS method for the quantification of Q808 in Rhesus monkey plasma. Furthermore, we applied this method to investigate the pharmacokinetics of Q808 in Rhesus monkeys. Methods: Samples containing diazepam as an internal standard (IS) were subjected to liquid-liquid extraction (LLE) and separated using a Zorbax Extend C18 column. The detection of Q808 and IS was performed using multiple reaction monitoring mode (MRM), specifically monitoring precursor-to-product ion transitions at m/z 297.9 to 213.9 and m/z 285.2 to 193.1 for Q808 and IS, respectively. For the pharmacokinetic study of Q808, a total of 30 healthy Rhesus monkeys (half male and half female) were administered single oral doses, single IV doses, or multiple oral doses of Q808. Blood samples were collected at predetermined time points for subsequent pharmacokinetic analysis. Results: The developed LC-MS/MS method exhibited linearity within the concentration range of 1.5-750 ng/mL with intra-day precision ≤8.3% and inter-day precision ≤14.6%. Additionally, accuracy was found to be ≤3.4%. In the pharmacokinetic study involving single oral doses of Q808 in Rhesus monkeys, Q808 was absorbed with a median time to peak plasma concentration ranging from 4.50-6.00 h and was eliminated with a terminal elimination half-life (t1/2) between 9.34-11.31 h. No definitive conclusion regarding linear pharmacokinetic characteristics could be drawn. The absolute bioavailability was determined as 20.95%, indicating limited systemic exposure after oral administration. Multiple dosing did not result in significant accumulation based on an accumulation factor Rac value of 1.31. Conclusion: We have successfully developed and validated a rapid yet sensitive LC-MS/MS method for quantifying levels of Q808 in rhesus monkey plasma for the first time. The determination method and pharmacokinetic characteristics of Q808 in rhesus monkey support the next steps in drug development .